The manifestations of bilingualism in Facebook and their impact on the Arabic language A field study of communica (مجلة إحالات, 2026)
Language is the best and most effective means of communication and reporting, as it is a system of symbols pronounced customary and easy to use that makes it the most effective means of dealing and understanding between individuals in various fields, whether in official institutions or in daily use among the general public, which resulted in what is known as conflict Colloquial with classical, which is termed as  bilingualism, this phenomenon that has spread widely in linguistic uses, and has become a form of internal linguistic conflict between them, and its spread has increased in social networking sites, especially Facebook.This is what prompted us to shed light on this subject, as the research presented the manifestations ofbilingualism in Facebook, initially talking about the manifestations of bilingualism, explaining its concept and clarifying its dangers and negative effects on the Arabic language.